Immune regulation by protein ubiquitination: roles of the E3 ligases VHL and Itch - Aki, Daisuke (Protein Cell, 2018)
Protein ubiquitination is an important means of post-translational modification which plays an essential role in the regulation of various aspects of leukocyte development and function. The specificity of ubiquitin tagging to a protein substrate is determined by E3 ubiquitin ligases via defined E3-substrate interactions. In this review, we will focus on two E3 ligases, VHL and Itch, to discuss the latest progress in understanding their roles in the differentiation and function of CD4(+) T helper cell subsets, the stability of regulatory T cells, effector function of CD8(+) T cells, as well as the development and maturation of innate lymphoid cells. The biological implications of these E3 ubiquitin ligases will be highlighted in the context of normal and dysregulated immune responses including the control of homeostasis, inflammation, auto-immune responses and anti-tumor immunity. Further elucidation of the ubiquitin system in immune cells will help in the design of new therapeutic interventions for human immunological diseases and cancer.